Optical pulse width measurements of sonoluminescence in cavitation-bubble fields - Matula, TJ; Roy, RA; Mourad, PD (Acoustical Society of America, 1998)
Optical pulse width measurements of sonoluminescence from cavitation-bubble fields have been obtained for two well-defined cavitation zones in an aqueous solution of Glycerin using a fast (650 ps rise-time) PMT and a fast (10 GS/S) digitizer. One zone corresponds to cavitation produced from an ultrasonic homogenizer. A lens was used to focus on a particular region of “streaming” sonoluminescence. A second, more localized cavitation zone was produced using a 2-in-diam PZT driving crystal in a rectangular fluid-filled container. Single-bubble sonoluminescence was used to characterize the response of the PMT to low-level light input. The measured rise-time and pulse width for sonoluminescence from cavitation fields is indicative of the response of the PMT and suggests that the pulse width of cavitation-field sonoluminescence is much less than 1.1 ns.